Sn-in-ga ternary doped copper powder, preparation method thereof and topcon photovoltaic copper paste
Patent Information
- Application Number
- CN202610830128.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-10
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2046-06-10
AI Technical Summary
但现有技术仍存在诸多不足:纯铜粉的高温抗氧化性较差,在烧结过程中易生成CuO、Cu2O等氧化产物,导致铜浆层电阻率显著升高;铜粉与银种子层的界面结合性薄弱,接触电阻较大,且易出现剥离现象,影响电极可靠性;单元素或二元元素掺杂的铜粉,难以同时兼顾导电性、抗氧化性与界面相容性三大核心需求,无法满足TOPCon电池叠层电极的高性能要求
[0016]本发明提供的Sn-In-Ga三元掺杂铜粉,采用Sn-In-Ga三元协同掺杂,从电子结构层面优化铜粉性能:Sn元素抑制铜粉高温氧化,In、Ga元素提升铜粉导电性,Sn-In-Ga三元协同作用实现了铜粉的抗氧化性与导电性的平衡,同时提升了铜粉与银种子层的界面浸润性,进而提高铜粉与银种子层的界面结合力,解决了现有铜浆高温氧化、界面接触差的痛点。
Smart Images

Figure SMS_41
Abstract
Description
Technical Field
[0001] This invention relates to the field of solar cell technology, and in particular to a Sn-In-Ga ternary doped copper powder and its preparation method, and TOPCon photovoltaic copper paste. Background Technology
[0002] As TOPCon (Tunnel Oxide Passivated Contact) cells iterate towards higher efficiency and refinement, TOPCon cells have become one of the next generation of mainstream photovoltaic cells due to their higher conversion efficiency.
[0003] The back of the TOPCon battery uses SiO X The poly-Si tunneling passivation structure places extremely high demands on the metallization process. Directly printing with copper paste can lead to problems such as high-temperature oxidation of copper powder, poor interfacial contact with the passivation layer, and copper atom diffusion into the passivation layer, resulting in passivation failure and ultimately causing a significant decrease in battery efficiency. Therefore, the mainstream metallization solution in the industry is a "silver seed layer + copper paste stacked printing". In this solution, the silver seed layer directly contacts the passivation layer to ensure good ohmic contact, while the copper paste layer acts as the main conductive layer, replacing the traditional all-silver electrode and achieving cost reduction and efficiency improvement. However, the existing technology still has many shortcomings: pure copper powder has poor high-temperature oxidation resistance and is prone to generating oxidation products such as CuO and Cu2O during sintering, resulting in a significant increase in the resistivity of the copper paste layer; the interfacial bonding between copper powder and the silver seed layer is weak, resulting in high contact resistance and easy delamination, affecting electrode reliability; copper powder doped with single or binary elements cannot simultaneously meet the three core requirements of conductivity, oxidation resistance, and interfacial compatibility, and cannot meet the high-performance requirements of TOPCon battery stacked electrodes. Summary of the Invention
[0004] The purpose of this invention is to provide a Sn-In-Ga ternary doped copper powder that has good conductivity, oxidation resistance and interfacial compatibility.
[0005] This invention provides a Sn-In-Ga ternary doped copper powder, comprising copper powder, tin, indium, and gallium, wherein the tin, indium, and gallium are attached to the surface of the copper powder; the atomic molar ratio of each element in the Sn-In-Ga ternary doped copper powder is Cu:Sn:In:Ga=(98.0~99.2):(0.2~0.8):(0.2~0.8):(0.2~0.8).
[0006] In one feasible manner, the copper powder has a particle size D50 of 0.6 μm to 2.0 μm and an oxygen content of ≤0.3 wt%.
[0007] The present invention also provides a method for preparing the Sn-In-Ga ternary doped copper powder as described above, comprising the following steps: S1: Dissolve tin salt, indium salt and gallium salt in a solvent and mix them evenly to obtain a doping precursor solution; S2: After adding copper powder to the doping precursor solution, ball milling is performed to adsorb tin ions, indium ions and gallium ions on the surface of the copper powder to obtain supported copper powder. S3: Dry the supported copper powder; S4: Under a reducing atmosphere, the supported copper powder is annealed to allow tin, indium and gallium to diffuse and solidify on the surface of the copper powder in atomic form, thereby obtaining a Cu(Sn-In-Ga) solid solution. S5: The Cu(Sn-In-Ga) solid solution is depolymerized and sieved to obtain Sn-In-Ga ternary doped copper powder.
[0008] In one possible implementation, in step S2 above, a first dispersant is also added to the doping precursor solution.
[0009] In one feasible manner, in step S3 above, the supported copper powder is vacuum dried under the following conditions: vacuum degree ≤10Pa, drying temperature 50℃~70℃, and drying time 2 hours~4 hours.
[0010] In one feasible approach, the specific steps for annealing the supported copper powder in step S4 above include: The supported copper powder is placed in a tube furnace, and then a reducing gas is introduced into the tube furnace to remove the air. The tube furnace is heated to 280°C to 450°C at a heating rate of 2°C / min to 5°C / min, and the supported copper powder is annealed at a constant temperature for 1 hour to 3 hours. After annealing, the supported copper powder is allowed to cool naturally to room temperature.
[0011] In one feasible manner, the reducing gas is a mixture of 95 vol% Ar and 5 vol% H2.
[0012] The present invention also provides a TOPCon photovoltaic copper paste, which, by mass parts, comprises: 84-90 parts of Sn-In-Ga ternary doped copper powder, 1-3 parts of glass powder, 7-12 parts of organic carrier, and 0.5-2 parts of additives; the organic carrier comprises organic resin and organic solvent, and the additives comprise thixotropic agent, second dispersant, and reducing agent; the Sn-In-Ga ternary doped copper powder is the Sn-In-Ga ternary doped copper powder as described above or prepared by the preparation method described above.
[0013] In one feasible embodiment, the glass powder is a Bi2O3-ZnO-B2O3 system glass powder, the melting point of the Bi2O3-ZnO-B2O3 system glass powder being 450℃~550℃; by mass percentage, the Bi2O3-ZnO-B2O3 system glass powder comprises: 55%~65% bismuth oxide, 15%~25% zinc oxide, and 10%~20% boron oxide.
[0014] In one feasible embodiment, the organic carrier comprises 6% to 12% by mass of organic resin and 88% to 94% by mass of organic solvent; And / or, the mass ratio of the second dispersant, thixotropic agent and reducing agent in the additive is (1.5~2.5):(0.8~1.2):(0.8~1.2).
[0015] In one feasible manner, the organic resin includes at least one of ethyl cellulose, cellulose acetate butyrate, polyvinyl butyral resin, acrylic resin, rosin resin, and epoxy resin. And / or, the organic solvent includes at least two of the following: dibutyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, benzyl alcohol, diethylene glycol dibutyl ether, diethylene glycol butyl ether, dodecyl alcohol ester, and diethylene glycol butyl ether acetate. And / or, the thixotropic agent includes at least one of polyamide wax, polyethylene wax, hydrogenated castor oil, and fumed silica; And / or, the dispersant comprises at least one of fatty acid polyoxyethylene ether, shea butter-based propylene diamine oleate, lecithin, oleic acid, polyvinylpyrrolidone, and polyethylene glycol; And / or, the reducing agent includes at least one of ascorbic acid and sodium hypophosphite.
[0016] The Sn-In-Ga ternary doped copper powder provided by this invention adopts Sn-In-Ga ternary synergistic doping to optimize the performance of copper powder from the electronic structure level: Sn element inhibits the high-temperature oxidation of copper powder, In and Ga elements improve the conductivity of copper powder, and the synergistic effect of Sn-In-Ga ternary doping achieves a balance between the oxidation resistance and conductivity of copper powder, while improving the interfacial wettability between copper powder and silver seed layer, thereby improving the interfacial bonding force between copper powder and silver seed layer, solving the pain points of high-temperature oxidation and poor interfacial contact of existing copper pastes. Detailed Implementation
[0017] The specific embodiments of the present invention will be described in further detail below. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. The terms "first," "second," "third," "fourth," etc. (if present) in the specification and claims of the present invention are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence.
[0018] This invention provides a Sn-In-Ga ternary doped copper powder for use in TOPCon photovoltaic copper paste. It comprises copper powder, tin (Sn), indium (In), and gallium (Ga), with copper powder as the matrix and tin, indium, and gallium adhering to the surface of the copper powder in atomic form. Specifically, the Sn-In-Ga ternary doped copper powder is a solid solution formed by tin, indium, and gallium adhering to the surface of the copper powder in atomic form. The atomic molar ratio of each element in the Sn-In-Ga ternary doped copper powder is Cu:Sn:In:Ga = (98.0~99.2):(0.2~0.8):(0.2~0.8):(0.2~0.8).
[0019] The roles of Sn, In, and Ga are as follows: 1. Sn can suppress the high-temperature oxidation of copper powder, reduce the 3D density of states of copper, and reduce the adsorption of oxygen atoms; 2. In and Ga, as donor dopant elements, provide free electrons to the copper lattice, increase the carrier concentration, and reduce the resistivity; 3. The ternary synergy of Sn, In, and Ga optimizes the electronic structure of copper powder, improves the compatibility of copper powder with silver seed layer and glass powder, and further reduces the interfacial resistance.
[0020] The atomic numbers of tin, indium, and gallium can be the same or different. The molar ratio of copper can be 98.0, 98.1, 98.2, 98.3, 98.4, 98.5, 98.6, 98.7, 98.8, 98.9, 99.0, 99.1, 99.2, etc., or any combination of these values. The molar ratio of tin can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, etc., or any combination of these values. The molar ratio of indium can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, etc., or any combination of these values. The molar ratio of gallium can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, etc., or any combination of these values.
[0021] The Sn-In-Ga ternary doped copper powder provided in this embodiment adopts Sn-In-Ga ternary synergistic doping to optimize the performance of copper powder from the electronic structure level: Sn element inhibits the high-temperature oxidation of copper powder, while In and Ga elements improve the conductivity of copper powder. The synergistic effect of Sn-In-Ga ternary doping achieves a balance between the oxidation resistance and conductivity of copper powder, while improving the interfacial wettability between copper powder and silver seed layer, thereby improving the interfacial bonding force between copper powder and silver seed layer, and solving the pain points of high-temperature oxidation and poor interfacial contact in existing copper pastes.
[0022] In one implementation, the sum of the atomic numbers of tin, indium, and gallium in the Sn-In-Ga ternary doped copper powder is 0.6 at% to 2.4 at% of the sum of the atomic numbers of copper, tin, indium, and gallium (i.e., the total atomic number), that is, the total doping ratio of tin, indium, and gallium is 0.6 at% to 2.4 at%. The total doping ratio of tin, indium, and gallium can be 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, etc., or any combination of the above values.
[0023] In one embodiment, the copper powder is commercially available copper powder, specifically atomized copper powder. The particle size D50 of the copper powder is 0.6 μm to 2.0 μm, and the oxygen content of the copper powder is ≤0.3 wt%.
[0024] In one embodiment, the Sn-In-Ga ternary doped copper powder has a particle size D50 of 0.6 μm to 2.0 μm, an oxygen content ≤0.2 wt%, and a resistivity ≤2.8 μΩ. cm.
[0025] This invention also provides a method for preparing the above-mentioned Sn-In-Ga ternary doped copper powder, comprising the following steps: S1: Dissolve tin salt, indium salt and gallium salt in a solvent and mix them evenly to obtain a doped precursor solution containing tin ions, indium ions and gallium ions; S2: Copper powder is added to the doping precursor solution and then ball-milled to adsorb tin ions, indium ions and gallium ions on the surface of the copper powder to obtain supported copper powder; wherein the atomic molar ratio of copper powder, tin salt, indium salt and gallium salt is Cu:Sn:In:Ga=(98.0~99.2):(0.2~0.8):(0.2~0.8):(0.2~0.8); S3: The supported copper powder is dried to obtain dried supported copper powder; S4: Under a reducing atmosphere, the supported copper powder is annealed to allow tin, indium and gallium to diffuse and solidify on the surface of the copper powder in atomic form (i.e., tin atoms, indium atoms and gallium atoms) to obtain a Cu(Sn-In-Ga) solid solution; S5: The Cu(Sn-In-Ga) solid solution is depolymerized and sieved to obtain Sn-In-Ga ternary doped copper powder.
[0026] Specifically, traditional copper powder doping methods often employ liquid-phase reduction to synthesize copper powder from the source. This process is not only complex and costly, but also difficult to control in terms of doping uniformity, hindering industrial mass production. In contrast, this embodiment uses commercially available copper powder for direct surface adsorption-solid-state diffusion doping, eliminating the need for copper powder synthesis from the source. This simplifies the doping process, reduces production costs and environmental impact, and avoids problems such as agglomeration, uneven particle size, and doping segregation inherent in liquid-phase reduction methods. It offers high feasibility for mass production and can be directly adapted to GW (Gigawatt) level photovoltaic production lines.
[0027] In one embodiment, the tin salt in step S1 above can be SnCl2. At least one of 2H2O (stannous chloride dihydrate), anhydrous SnCl2 (stannous chloride anhydrous), SnSO4 (stannous sulfate), Sn(acac)2 (stannous acetylacetone), and Sn(CH3COO)2 (stannous acetate).
[0028] The indium salt can be selected from InCl3 (indium chloride) or In(NO3)3. At least one of xH2O (indium nitrate), In(acac)3 (indium acetylacetone), and In(CH3COO)3 (indium acetate).
[0029] The gallium salt can be selected from GaCl3 (gallium chloride) or Ga(NO3)3. At least one of xH2O (gallium nitrate), Ga(acac)3 (gallium acetylacetonate), and Ga(CH3COO)3 (gallium acetate).
[0030] The purity of the tin salt, the indium salt, and the gallium salt is ≥99.8%.
[0031] The solvent can be at least one of anhydrous ethanol and isopropanol.
[0032] In one implementation, in step S1 above, the total concentration of metal ions in the doping precursor solution (i.e., the sum of the concentrations of tin ions, indium ions, and gallium ions) can be 0.1 mol / L to 0.35 mol / L, specifically 0.1 mol / L, 0.12 mol / L, 0.15 mol / L, 0.18 mol / L, 0.25 mol / L, 0.28 mol / L, 0.3 mol / L, 0.35 mol / L, etc., or any combination of the above values.
[0033] As one implementation method, in step S1 above, to prevent hydrolysis of the doping precursor solution, a certain amount of hydrolysis inhibitor can be added to the doping precursor solution. The hydrolysis inhibitor can be determined according to the type of tin salt, indium salt, and gallium salt, for example, SnCl2, indium salt, and gallium salt respectively. When using 2H₂O, InCl₃, and GaCl₃, concentrated hydrochloric acid can be used as the hydrolysis inhibitor. The amount of hydrolysis inhibitor added can be, for example, 0.1 mL to 0.15 mL.
[0034] As one implementation method, step S1 above can specifically be: SnCl2 2H₂O, InCl₃, and GaCl₃ are dissolved in anhydrous ethanol in atomic ratios and stirred for 15–20 minutes until SnCl₂ is obtained. 2H2O, InCl3, and GaCl3 are completely dissolved and mixed evenly to form a uniform and transparent doped precursor solution; if slight hydrolysis occurs, 2-3 drops of concentrated hydrochloric acid can be added to suppress it.
[0035] In one embodiment, in step S2 above, an appropriate amount of a first dispersant is added to the doping precursor solution to ensure that the copper powder is uniformly dispersed in the doping precursor solution and that tin ions, indium ions, and gallium ions are uniformly adsorbed on the surface of the copper powder. The first dispersant may be at least one of fatty acid polyoxyethylene ether, oleic acid, and polyvinylpyrrolidone (PVP).
[0036] As one implementation method, step S2 can be specifically as follows: the screened copper powder is added to the doping precursor solution according to the atomic ratio, and an appropriate amount of PVP dispersant is added. The mixture is ball-milled for 30-60 minutes with a ball-to-material ratio of 5:1 (zirconia balls are added during ball milling, and the mass ratio of zirconia balls to material is 5:1). The ball milling speed is 200-300 r / min, so that Sn, In, and Ga dopant ions are uniformly adsorbed on the surface of the copper powder to obtain supported copper powder with doped ions.
[0037] As one implementation method, in step S3 above, the supported copper powder is vacuum dried under the following conditions: vacuum degree ≤ 10 Pa, drying temperature 50℃~70℃, and drying time 2 hours~4 hours.
[0038] As one implementation method, step S3 above can specifically be as follows: placing the supported copper powder in a vacuum drying oven and drying it for 2 to 4 hours under the conditions of vacuum degree ≤10Pa and drying temperature 50℃~70℃ to obtain dried supported copper powder (the moisture content of the supported copper powder is ≤0.1wt%).
[0039] As one implementation method, the specific steps for annealing the supported copper powder in step S4 above include: The supported copper powder is placed in a tube furnace, and then a reducing gas is introduced into the tube furnace to remove the air. The tube furnace is heated to 280°C to 450°C at a heating rate of 2°C / min to 5°C / min, and the supported copper powder is annealed at a constant temperature for 1 hour to 3 hours. After annealing, the supported copper powder is allowed to cool naturally to room temperature (e.g., 20°C to 30°C, or 25°C).
[0040] The reducing gas is a mixture of 95 vol% Ar and 5 vol% H2, meaning the mixture contains 95% argon and 5% hydrogen by volume. Argon acts as an inert protective gas, purging air from the tube furnace and providing inert protection, while hydrogen acts as a reducing gas, preventing the copper powder from oxidizing.
[0041] As one implementation method, step S4 can be specifically as follows: placing the supported copper powder into a tube furnace, and then introducing a mixed atmosphere of 95 vol% Ar + 5 vol% H2 (flow rate 80 mL / min) into the tube furnace for 30 min to remove air (oxygen content ≤ 50 ppm) from the tube furnace; heating the tube furnace to 280°C to 450°C at a heating rate of 2°C / min to 5°C / min, and isothermal annealing the supported copper powder for 1 to 3 hours; after annealing, naturally cooling the supported copper powder to room temperature, allowing tin, indium, and gallium to diffuse and solidify on the surface of the copper powder in atomic form to obtain a Cu(Sn-In-Ga) solid solution.
[0042] In one implementation, the deagglomeration process in step S5 above involves breaking up the clumps in the Cu(Sn-In-Ga) solid solution to disperse them (in step S4, the annealed Cu(Sn-In-Ga) solid solution may agglomerate), facilitating subsequent sieving. This deagglomeration process can be mechanical, specifically using a powder deagglomeration and dispersion machine to disperse the Cu(Sn-In-Ga) solid solution, or by ball milling, stirring, air jet milling, ultrasonic vibration, or other methods.
[0043] As one implementation method, in step S5 above, the Cu(Sn-In-Ga) solid solution can be sieved through a 300-500 mesh screen.
[0044] This invention also provides a TOPCon photovoltaic copper paste, which, by mass parts, comprises: 84-90 parts of Sn-In-Ga ternary doped copper powder, 1-3 parts of glass powder, 7-12 parts of organic carrier, and 0.5-2 parts of additives; the organic carrier comprises organic resin and organic solvent, and the additives comprise thixotropic agent, second dispersant, and reducing agent; the Sn-In-Ga ternary doped copper powder is the Sn-In-Ga ternary doped copper powder as described above or prepared by the preparation method described above.
[0045] The mass fractions of Sn-In-Ga ternary doped copper powder can be 84, 85, 86, 87, 88, 89, 90 parts, or any combination thereof. The mass fractions of glass powder can be 1, 1.5, 2, 2.5, 3 parts, or any combination thereof. The mass fractions of the organic carrier can be 7, 8, 9, 10, 11, 12 parts, or any combination thereof. The mass fractions of the additives can be 0.5, 1, 1.5, 2 parts, or any combination thereof.
[0046] In one embodiment, the glass powder is a low-melting-point glass powder. Specifically, the glass powder is a Bi2O3-ZnO-B2O3 system glass powder, which, by mass percentage, comprises: 55%~65% bismuth oxide (Bi2O3), 15%~25% zinc oxide (ZnO), and 10%~20% boron oxide (B2O3), with the sum of the three being 100%, and an impurity content ≤0.5%. The Bi2O3-ZnO-B2O3 system glass powder has a melting point of 450℃~550℃, a particle size D50 of 1.0~3.0μm, a softening temperature of 400℃~480℃, and a flow temperature of 500℃~580℃; it does not react with copper or silver, does not corrode the passivation layer, and can achieve interface wetting, diffusion blocking, passivation layer protection, and auxiliary forming functions.
[0047] The mass percentage of bismuth oxide can be 55%, 58%, 60%, 62%, 65%, or any combination thereof. The mass percentage of zinc oxide can be 15%, 18%, 20%, 22%, 25%, or any combination thereof. The mass percentage of boron oxide can be 10%, 12%, 15%, 18%, 20%, or any combination thereof.
[0048] Specifically, the glass powder used in existing copper pastes has a high melting point or an unsuitable composition, making it unsuitable for the co-sintering process of copper paste and silver seed layer. This results in either the inability to form an effective diffusion barrier layer to suppress copper diffusion, or damage to the SiOx / poly-Si passivation layer on the back of the TOPCon battery, thus affecting battery performance. In this embodiment, Bi2O3-ZnO-B2O3 system glass powder is added to the copper paste formulation. During sintering, a dense diffusion barrier layer is formed in situ, effectively suppressing the diffusion of copper atoms to the SiOx / poly-Si passivation layer on the back of the TOPCon battery, preventing passivation failure, and ensuring battery conversion efficiency and reliability.
[0049] As one implementation method, the preparation steps of the Bi2O3-ZnO-B2O3 system glass powder include: Bismuth oxide, zinc oxide, and boron oxide were weighed out according to the above-mentioned mass percentages, mixed evenly, and then placed in a high-temperature furnace. The mixture was melted at 1000℃~1200℃ for 30-60 minutes, stirring constantly to ensure no bubbles or unmelted particles, resulting in molten glass. The molten glass was then rapidly poured into deionized water for quenching, forming glass fragments. These fragments were crushed, ground, and sieved through a 300-500 mesh sieve to obtain low-melting-point glass powder (i.e., Bi₂O₃-ZnO-B₂O₃ system glass powder) that meets the above performance parameters. This powder was then sealed and stored for later use.
[0050] In one embodiment, the organic carrier contains 6% to 12% organic resin by mass and 88% to 94% organic solvent by mass, with the sum of the two being 100%. The mass percentage of organic resin can be 6%, 7%, 8%, 9%, 10%, 11%, 12%, or any combination thereof; the mass percentage of organic solvent can be 88%, 89%, 90%, 91%, 92%, 93%, 94%, or any combination thereof.
[0051] In one embodiment, the organic resin includes at least one of ethyl cellulose, cellulose acetate butyrate, polyvinyl butyral resin, acrylic resin, rosin resin, and epoxy resin.
[0052] The organic solvent includes at least two of the following: dibutyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, benzyl alcohol, diethylene glycol dibutyl ether, diethylene glycol butyl ether, dodecyl alcohol ester, and diethylene glycol butyl ether acetate. By using at least two different organic solvents with different boiling points, a gradient evaporation can be formed during drying, preventing delamination and cracking of the copper paste layer during drying.
[0053] Specifically, the organic carrier formulations used in existing copper pastes are unclear and their performance is unstable, easily leading to uneven dispersion of copper powder and glass powder, resulting in problems such as printing line breaks and ink overflow. Furthermore, they cannot be completely volatilized during the sintering process, and residual impurities can affect the conductivity and interfacial adhesion of the electrodes. The organic carrier with the above-mentioned formulation used in this embodiment can solve the above problems.
[0054] As one implementation method, the preparation steps of the organic carrier include: Weigh the organic resin and organic solvent according to the above-mentioned mass percentages, place them in a container equipped with a stirring and heating device, heat to 60℃~70℃, stir for 30min~40min until all components are completely dissolved, forming a uniform, transparent, viscous liquid. Then filter through a 100-mesh filter to remove undissolved impurities and air bubbles, cool to room temperature, and obtain an organic carrier that meets the above performance parameters. Seal and store for later use (storage temperature 20℃~25℃, avoid direct sunlight).
[0055] In one embodiment, the mass ratio of the second dispersant, thixotropic agent, and reducing agent in the additive is (1.5~2.5):(0.8~1.2):(0.8~1.2). Specifically, the mass ratio of the second dispersant can be 1.5, 1.8, 2.0, 2.3, 2.5, etc., or any combination of the above values; the mass ratio of the thixotropic agent can be 0.8, 0.9, 1.0, 1.1, 1.2, etc., or any combination of the above values; and the mass ratio of the reducing agent can be 0.8, 0.9, 1.0, 1.1, 1.2, etc., or any combination of the above values.
[0056] In one embodiment, the thixotropic agent includes at least one of polyamide wax, polyethylene wax, hydrogenated castor oil, and fumed silica.
[0057] The dispersant includes at least one of fatty acid polyoxyethylene ether, shea butter-based propylene diamine oleate, lecithin, oleic acid, polyvinylpyrrolidone (PVP), and polyethylene glycol.
[0058] The reducing agent includes at least one of ascorbic acid and sodium hypophosphite.
[0059] As one implementation method, the preparation steps of TOPCon photovoltaic copper paste include: Add Sn-In-Ga ternary doped copper powder, glass powder, organic carrier and additives to a planetary mixer according to the mass fractions, and stir at 400~500r / min for 30~40min until initially mixed evenly. The mixture is then ground with a three-roll mill until the fineness is ≤10μm, and then vacuum degassed for 15~20min to remove air bubbles, thus obtaining the finished TOPCon photovoltaic copper paste.
[0060] This invention also provides a TOPCon battery, wherein a passivation layer is provided on the back side of the TOPCon battery, and the passivation layer is SiO. X / poly-Si passivation layer, SiO X The poly-Si passivation layer comprises an ultrathin silicon dioxide (SiO2) tunneling oxide layer and a phosphorus-doped polycrystalline silicon (poly-Si) layer, which together constitute a tunneling passivation structure. A silver seed layer is disposed on the surface of the passivation layer, and a copper paste layer is disposed on the surface of the silver seed layer. The silver seed layer and the copper paste layer constitute a stacked electrode structure; the copper paste layer is obtained by sintering the aforementioned TOPCon photovoltaic copper paste.
[0061] As one implementation method, the preparation steps of the silver seed layer and the copper paste layer include: A silver seed layer is printed (screen-printed) on the passivation layer on the back of the TOPCon cell, and then dried (e.g., at 150℃ for 5-8 min). Next, TOPCon photovoltaic copper paste is printed on the silver seed layer, and then dried (e.g., at 150℃ for 2-3 min). Finally, co-sintering is performed to obtain the silver seed layer and the copper paste layer. The sintering parameters are as follows: in a N2+H2 mixed atmosphere (oxygen content ≤50ppm), the temperature is increased to 680-740℃ at a heating rate of 5-8℃ / min, and sintered at this temperature for 5-8 min, followed by natural cooling to room temperature.
[0062] The beneficial effects of this embodiment include: 1. The Sn-In-Ga ternary synergistic doping method optimizes the performance of copper powder from the electronic structure level: Sn element inhibits the high-temperature oxidation of copper powder, while In and Ga elements enhance the conductivity of copper powder. The synergistic effect of Sn-In-Ga ternary doping achieves a balance between the oxidation resistance and conductivity of copper powder, while improving the interfacial wettability between copper powder and silver seed layer, thereby improving the interfacial bonding force between copper powder and silver seed layer, and solving the pain points of high-temperature oxidation and poor interfacial contact of existing copper paste.
[0063] 2. Commercial copper powder is used for direct surface adsorption-solid diffusion doping, eliminating the need to synthesize copper powder from the source. This simplifies the doping process, reduces production costs and environmental pressure, and avoids problems such as agglomeration, uneven particle size, and doping segregation that exist in the liquid phase reduction method for preparing copper powder. It has high feasibility for mass production and can be directly adapted to GW-level photovoltaic production lines.
[0064] 3. Adding Bi2O3-ZnO-B2O3 system glass powder to the copper paste formula forms a dense diffusion barrier layer in situ during sintering, which effectively inhibits the diffusion of copper atoms to the SiOx / poly-Si passivation layer on the back of the TOPCon battery, avoids passivation failure, and ensures battery conversion efficiency and reliability.
[0065] 4. It is compatible with the "silver seed layer + copper paste layer" stacked electrode structure on the back of TOPCon batteries. The silver seed layer ensures ohmic contact, while the copper paste layer dominates conductivity. This significantly reduces silver loss on the back (70%~90%) while ensuring that the battery conversion efficiency loss is ≤0.05%, achieving the dual goals of cost reduction and efficiency improvement, and has extremely high industrial application value.
[0066] [Example 1] The TOPCon photovoltaic copper paste in this embodiment comprises, by mass parts: 87 parts of Sn-In-Ga ternary doped copper powder, 2 parts of Bi2O3-ZnO-B2O3 system glass powder, 9 parts of organic carrier, and 2 parts of additives.
[0067] The Sn-In-Ga ternary doped copper powder has an atomic molar ratio of Cu:Sn:In:Ga = 98.5:0.5:0.5:0.5, a D50 of 1.2 μm, an oxygen content ≤0.2 wt%, and a resistivity ≤2.8 μΩ. cm. The copper powder used is atomized copper powder (manufacturer: Anhui Superlattice New Material Technology Co., Ltd., product model: n-MP-Cu-S-1200), with a D50 of 1.2μm and an oxygen content ≤0.3wt%. The doping source is SnCl2. 2H2O (manufacturer: Zhuzhou Aoboda New Materials Co., Ltd., product model: ABD-Sn-995), InCl3 (manufacturer: Zhuzhou Aoboda New Materials Co., Ltd., product model: ABD-InCl3-5N), GaCl3 (manufacturer: Zhuzhou Aoboda New Materials Co., Ltd., product model: ABD-GaCl3-5N).
[0068] The Bi2O3-ZnO-B2O3 system has the following glass powder composition by mass percentage: Bi2O3: 60%, ZnO: 20%, B2O3: 20%, melting point 500℃, and D50 2.0μm.
[0069] The organic carrier is a mixture of ethyl cellulose (manufacturer: Eastman Chemical Company, product model: CAB-381-0.5), terpineol (manufacturer: Jiangsu Yida Chemical Co., Ltd., product model: YD-T89), and butyl carbitol acetate (manufacturer: Nanjing Weier Chemical Co., Ltd., product model: WE-BCA) in a mass ratio of 1:6:3. The additives are a mixture of PVP (polyvinylpyrrolidone) (manufacturer: BASF AG, product model: Luvitec K90), polyamide wax (manufacturer: Guangdong Deqian New Materials Co., Ltd., product model: DA-620), and ascorbic acid (manufacturer: CSPC Weisheng Pharmaceutical Co., Ltd., product model: VC-E) in a mass ratio of 2:1:1.
[0070] I. Preparation steps of TOPCon photovoltaic copper paste: (1) Preparation of Sn-In-Ga ternary doped copper powder: 1. Preparation of doping precursor solution: Weigh out SnCl2 according to the atomic molar ratio of Cu:Sn:In:Ga = 98.5:0.5:0.5:0.5. 1.80 g of 2H2O, 1.77 g of InCl3, and 1.41 g of GaCl3 were dissolved in 100 mL of anhydrous ethanol and stirred for 18 min to obtain a uniform and transparent doped precursor solution.
[0071] 2. Copper powder loaded with doping elements: Weigh 100g of atomized copper powder and add it to the above doping precursor solution. Ball mill for 45min at a ball milling speed of 250r / min and a ball-to-material ratio of 5:1 to obtain loaded copper powder.
[0072] 3. Low-temperature vacuum drying: Place the supported copper powder in a vacuum drying oven and dry it for 3 hours under the conditions of vacuum degree ≤10Pa and drying temperature 60℃ to obtain dried supported copper powder.
[0073] 4. Reducing atmosphere annealing and diffusion: Dry supported copper powder is placed in a tube furnace, and a mixed atmosphere of 95 vol% Ar + 5 vol% H2 is introduced into the tube furnace at a flow rate of 80 mL / min. After the atmosphere is introduced for 30 min, the tube furnace is heated to 400 °C at a heating rate of 3 °C / min, and the supported copper powder is annealed at a constant temperature for 2 hours. After annealing, the supported copper powder is naturally cooled to room temperature to obtain Cu(Sn-In-Ga) solid solution.
[0074] 5. Depolymerization and sieving: The Cu(Sn-In-Ga) solid solution is depolymerized and sieved through a 400-mesh sieve to obtain Sn-In-Ga ternary doped copper powder.
[0075] (2) Preparation of organic carriers: Weigh out 1 part ethyl cellulose, 6 parts terpineol, and 3 parts butyl carbitol acetate, mix them, heat to 65°C, stir until completely dissolved, filter to remove bubbles, and obtain the organic carrier.
[0076] (3) Preparation of TOPCon photovoltaic copper paste: Weigh out 87 parts of Sn-In-Ga ternary doped copper powder, 2 parts of Bi2O3-ZnO-B2O3 system glass powder, 9 parts of organic carrier and 2 parts of additives according to the mass fraction, add them to a planetary mixer and stir at 450 r / min for 35 min; then grind them with a three-roll mill (pressure 0.4 MPa) until the fineness is ≤5 μm, and degas under vacuum for 18 min to obtain TOPCon photovoltaic copper paste.
[0077] II. Fabrication of stacked electrodes on the back of the TOPCon battery: 1. Printing silver seed layer: Silver paste is screen-printed onto the SiOx / poly-Si passivation layer on the back of the TOPCon battery with a thickness of 2μm, and dried at 150℃ for 6min.
[0078] 2. Overprinting copper paste: The prepared TOPCon photovoltaic copper paste is overprinted on the surface of the silver seed layer with a thickness of 15μm and dried at 150℃ for 2.5min.
[0079] 3. Co-sintering: Under a mixed atmosphere of N2+H2 (oxygen content ≤50ppm), the temperature is increased to 650℃ at a heating rate of 6℃ / min, and sintered at a constant temperature for 6min. Then, it is naturally cooled to room temperature to form a multilayer electrode.
[0080] The contact resistance of the stacked electrode was measured to be 0.05Ω. cm², volume resistivity 2.9 μΩ The resistivity increased by 7% after baking at 200℃ for 1 hour. The TOPCon cell using this stacked electrode has a fill factor of 84.2%, a back-side silver loss of 85% compared to the all-silver electrode, and a cell conversion efficiency loss of 0.04%, demonstrating excellent performance.
[0081] [Example 2] The TOPCon photovoltaic copper paste in this embodiment comprises, by mass parts: 84 parts Sn-In-Ga ternary doped copper powder, 3 parts Bi2O3-ZnO-B2O3 system glass powder, 11 parts organic carrier, and 2 parts additives.
[0082] The Sn-In-Ga ternary doped copper powder has an atomic molar ratio of Cu:Sn:In:Ga = 99.2:0.2:0.3:0.3, a D50 of 1.2 μm, an oxygen content ≤0.2 wt%, and a resistivity ≤2.8 μΩ. cm. Atomized copper powder with a D50 of 1.2 μm and an oxygen content ≤0.3 wt% was selected. SnCl2 was used as the doping source. 2H2O, InCl3, GaCl3.
[0083] The Bi2O3-ZnO-B2O3 system has the following glass powder composition by mass percentage: Bi2O3: 55%, ZnO: 25%, B2O3: 20%, melting point 530℃, and D50 2.0μm.
[0084] The organic carrier is composed of ethyl cellulose, terpineol, and butyl carbitol acetate in a mass ratio of 1:6:3. The additives are composed of PVP (polyvinylpyrrolidone), polyamide wax, and ascorbic acid in a mass ratio of 2:1:1.
[0085] I. Preparation steps of TOPCon photovoltaic copper paste: (1) Preparation of Sn-In-Ga ternary doped copper powder: 1. Preparation of doping precursor solution: Weigh out SnCl2 according to the atomic molar ratio of Cu:Sn:In:Ga = 99.2:0.2:0.3:0.3. 0.72 g of 2H2O, 1.05 g of InCl3, and 0.84 g of GaCl3 were dissolved in 100 mL of anhydrous ethanol and stirred for 18 min to obtain a uniform and transparent doped precursor solution.
[0086] 2. Copper powder loaded with doping elements: Weigh 100g of atomized copper powder and add it to the above doping precursor solution. Ball mill for 45min at a ball milling speed of 250r / min and a ball-to-material ratio of 5:1 to obtain loaded copper powder.
[0087] 3. Low-temperature vacuum drying: Place the supported copper powder in a vacuum drying oven and dry it for 3 hours under the conditions of vacuum degree ≤10Pa and drying temperature 60℃ to obtain dried supported copper powder.
[0088] 4. Reducing atmosphere annealing and diffusion: Dry supported copper powder is placed in a tube furnace, and a mixed atmosphere of 95 vol% Ar + 5 vol% H2 is introduced into the tube furnace at a flow rate of 80 mL / min. After 30 min of atmosphere introduction, the tube furnace is heated to 280 °C at a heating rate of 2 °C / min, and the supported copper powder is annealed at a constant temperature for 3 hours. After annealing, the supported copper powder is naturally cooled to room temperature to obtain Cu(Sn-In-Ga) solid solution.
[0089] 5. Depolymerization and sieving: The Cu(Sn-In-Ga) solid solution is depolymerized and sieved through a 400-mesh sieve to obtain Sn-In-Ga ternary doped copper powder.
[0090] (2) Preparation of organic carriers: Weigh out 1 part ethyl cellulose, 6 parts terpineol, and 3 parts butyl carbitol acetate, mix them, heat to 65°C, stir until completely dissolved, filter to remove bubbles, and obtain the organic carrier.
[0091] (3) Preparation of TOPCon photovoltaic copper paste: Weigh out 84 parts of Sn-In-Ga ternary doped copper powder, 3 parts of Bi2O3-ZnO-B2O3 system glass powder, 11 parts of organic carrier and 2 parts of additives according to the mass fraction, add them to a planetary mixer and stir at 450 r / min for 35 min; then grind them with a three-roll mill (pressure 0.4 MPa) to a fineness of ≤5 μm, and degas under vacuum for 18 min to obtain TOPCon photovoltaic copper paste.
[0092] II. Fabrication of stacked electrodes on the back of the TOPCon battery: 1. Printing silver seed layer: Silver paste is screen-printed onto the SiOx / poly-Si passivation layer on the back of the TOPCon battery with a thickness of 2μm, and dried at 150℃ for 6min.
[0093] 2. Overprinting copper paste: The prepared TOPCon photovoltaic copper paste is overprinted on the surface of the silver seed layer with a thickness of 15μm and dried at 150℃ for 2.5min.
[0094] 3. Co-sintering: Under a mixed atmosphere of N2+H2 (oxygen content ≤50ppm), the temperature is increased to 650℃ at a heating rate of 6℃ / min, and sintered at a constant temperature for 6min. Then, it is naturally cooled to room temperature to form a multilayer electrode.
[0095] The contact resistance of the stacked electrode was measured to be 0.06Ω. cm², volume resistivity 3.0 μΩ The resistivity increased by 8% after baking at 200℃ for 1 hour. The TOPCon cell using this stacked electrode has a fill factor of 83.5%, a 70% reduction in back-side silver loss compared to the all-silver electrode, and a cell conversion efficiency loss of 0.05%, demonstrating excellent performance.
[0096] [Example 3] The TOPCon photovoltaic copper paste in this embodiment comprises, by mass parts: 90 parts Sn-In-Ga ternary doped copper powder, 1 part Bi2O3-ZnO-B2O3 system glass powder, 7 parts organic carrier, and 2 parts additives.
[0097] The Sn-In-Ga ternary doped copper powder has an atomic molar ratio of Cu:Sn:In:Ga = 98.0:0.8:0.6:0.6, a D50 of 1.2 μm, an oxygen content ≤0.2 wt%, and a resistivity ≤2.8 μΩ. cm. Atomized copper powder with a D50 of 1.2 μm and an oxygen content ≤0.3 wt% was selected. SnCl2 was used as the doping source. 2H2O, InCl3, GaCl3.
[0098] The Bi2O3-ZnO-B2O3 system has the following glass powder composition by mass percentage: Bi2O3: 65%, ZnO: 15%, B2O3: 20%, melting point 480℃, and D50 2.0μm.
[0099] The organic carrier is composed of ethyl cellulose, terpineol, and butyl carbitol acetate in a mass ratio of 1:6:3. The additives are composed of PVP (polyvinylpyrrolidone), polyamide wax, and ascorbic acid in a mass ratio of 2:1:1.
[0100] I. Preparation steps of TOPCon photovoltaic copper paste: (1) Preparation of Sn-In-Ga ternary doped copper powder: 1. Preparation of doping precursor solution: Weigh out SnCl2 according to the atomic molar ratio of Cu:Sn:In:Ga = 98.0:0.8:0.6:0.6. 2.9 g of 2H2O, 2.13 g of InCl3, and 1.7 g of GaCl3 were dissolved in 100 mL of anhydrous ethanol and stirred for 18 min to obtain a uniform and transparent doped precursor solution.
[0101] 2. Copper powder loaded with doping elements: Weigh 100g of atomized copper powder and add it to the above doping precursor solution. Ball mill for 45min at a ball milling speed of 250r / min and a ball-to-material ratio of 5:1 to obtain loaded copper powder.
[0102] 3. Low-temperature vacuum drying: Place the supported copper powder in a vacuum drying oven and dry it for 3 hours under the conditions of vacuum degree ≤10Pa and drying temperature 60℃ to obtain dried supported copper powder.
[0103] 4. Reducing atmosphere annealing and diffusion: Dry supported copper powder is placed in a tube furnace, and a mixed atmosphere of 95 vol% Ar + 5 vol% H2 is introduced into the tube furnace at a flow rate of 80 mL / min. After the atmosphere is introduced for 30 min, the tube furnace is heated to 450 °C at a heating rate of 5 °C / min, and the supported copper powder is annealed at a constant temperature for 1 hour. After annealing, the supported copper powder is naturally cooled to room temperature to obtain Cu(Sn-In-Ga) solid solution.
[0104] 5. Depolymerization and sieving: The Cu(Sn-In-Ga) solid solution is depolymerized and sieved through a 400-mesh sieve to obtain Sn-In-Ga ternary doped copper powder.
[0105] (2) Preparation of organic carriers: Weigh out 1 part ethyl cellulose, 6 parts terpineol, and 3 parts butyl carbitol acetate, mix them, heat to 65°C, stir until completely dissolved, filter to remove bubbles, and obtain the organic carrier.
[0106] (3) Preparation of TOPCon photovoltaic copper paste: Weigh out 90 parts by mass of Sn-In-Ga ternary doped copper powder, 1 part of Bi2O3-ZnO-B2O3 system glass powder, 7 parts of organic carrier and 2 parts of additives, add them to a planetary mixer and stir at 450 r / min for 35 min; then grind them with a three-roll mill (pressure 0.4 MPa) until the fineness is ≤5 μm, and degas under vacuum for 18 min to obtain TOPCon photovoltaic copper paste.
[0107] II. Fabrication of stacked electrodes on the back of the TOPCon battery: 1. Printing silver seed layer: Silver paste is screen-printed onto the SiOx / poly-Si passivation layer on the back of the TOPCon battery with a thickness of 2μm, and dried at 150℃ for 6min.
[0108] 2. Overprinting copper paste: The prepared TOPCon photovoltaic copper paste is overprinted on the surface of the silver seed layer with a thickness of 15μm and dried at 150℃ for 2.5min.
[0109] 3. Co-sintering: Under a mixed atmosphere of N2+H2 (oxygen content ≤50ppm), the temperature is increased to 650℃ at a heating rate of 6℃ / min, and sintered at a constant temperature for 6min. Then, it is naturally cooled to room temperature to form a multilayer electrode.
[0110] The contact resistance of the stacked electrode was measured to be 0.04Ω. cm², volume resistivity 2.7 μΩ After baking at 200℃ for 1 hour, the resistivity increased by 6%. The TOPCon cell using this stacked electrode has a fill factor of 84.5%, a 90% reduction in back-side silver loss compared to the all-silver electrode, and a cell conversion efficiency loss of 0.03%, making it the best performing embodiment.
[0111] [Comparative Example 1] The TOPCon photovoltaic copper paste in this comparative example, by mass parts, comprises: 87 parts of pure atomized copper powder, 2 parts of Bi2O3-ZnO-B2O3 system glass powder, 9 parts of organic carrier, and 2 parts of additives.
[0112] The copper powder used is commercially available atomized copper powder with a D50 of 1.2μm and an oxygen content of ≤0.3wt%, and it is not doped with any elements.
[0113] The Bi2O3-ZnO-B2O3 system has the following glass powder composition by mass percentage: Bi2O3: 60%, ZnO: 20%, B2O3: 20%, melting point 500℃, and D50 2.0μm.
[0114] The organic carrier is composed of ethyl cellulose, terpineol, and butyl carbitol acetate in a mass ratio of 1:6:3. The additives are composed of PVP (polyvinylpyrrolidone), polyamide wax, and ascorbic acid in a mass ratio of 2:1:1.
[0115] I. Preparation steps of TOPCon photovoltaic copper paste: (1) Use undoped commercial pure atomized copper powder without loading of doping elements or annealing diffusion treatment.
[0116] (2) Preparation of organic carriers: Weigh out 1 part ethyl cellulose, 6 parts terpineol, and 3 parts butyl carbitol acetate, mix them, heat to 65°C, stir until completely dissolved, filter to remove bubbles, and obtain the organic carrier.
[0117] (3) Preparation of TOPCon photovoltaic copper paste: Weigh out 87 parts of pure atomized copper powder, 2 parts of Bi2O3-ZnO-B2O3 system glass powder, 9 parts of organic carrier and 2 parts of additives according to the mass ratio, add them to a planetary mixer and stir at 450 r / min for 35 min; then grind them with a three-roll mill (pressure 0.4 MPa) until the fineness is ≤5μm, and degas under vacuum for 18 min to obtain TOPCon photovoltaic copper paste.
[0118] II. Fabrication of stacked electrodes on the back of the TOPCon battery: 1. Printing silver seed layer: Silver paste is screen-printed onto the SiOx / poly-Si passivation layer on the back of the TOPCon battery with a thickness of 2μm, and dried at 150℃ for 6min.
[0119] 2. Overprinting copper paste: The prepared TOPCon photovoltaic copper paste is overprinted on the surface of the silver seed layer with a thickness of 15μm and dried at 150℃ for 2.5min.
[0120] 3. Co-sintering: Under a mixed atmosphere of N2+H2 (oxygen content ≤50ppm), the temperature is increased to 650℃ at a heating rate of 6℃ / min, and sintered at a constant temperature for 6min. Then, it is naturally cooled to room temperature to form a multilayer electrode.
[0121] The contact resistance of the stacked electrode was measured to be 0.12Ω. cm², volume resistivity 4.2 μΩ cm, after baking at 200℃ for 1 hour, the resistivity increased by 25%. The TOPCon battery using this stacked electrode has a fill factor of 82.1% and a battery conversion efficiency loss of 0.18%, which is significantly worse than that of Example 1.
[0122] [Comparative Example 2] The TOPCon photovoltaic copper paste in this comparative example, by mass parts, comprises: 87 parts of Sn-doped copper powder, 2 parts of Bi2O3-ZnO-B2O3 system glass powder, 9 parts of organic carrier, and 2 parts of additives.
[0123] The Sn-doped copper powder has an atomic molar ratio of Cu:Sn = 98.5:0.5, a D50 of 1.2 μm, and an oxygen content ≤0.2 wt%. Atomized copper powder with a D50 of 1.2 μm and an oxygen content ≤0.3 wt% is used. Only SnCl2 is used as the doping source. 2H2O, without adding In or Ga elements.
[0124] The Bi2O3-ZnO-B2O3 system has the following glass powder composition by mass percentage: Bi2O3: 60%, ZnO: 20%, B2O3: 20%, melting point 500℃, and D50 2.0μm.
[0125] The organic carrier is composed of ethyl cellulose, terpineol, and butyl carbitol acetate in a mass ratio of 1:6:3. The additives are composed of PVP (polyvinylpyrrolidone), polyamide wax, and ascorbic acid in a mass ratio of 2:1:1.
[0126] I. Preparation steps of TOPCon photovoltaic copper paste: (1) Preparation of Sn-doped copper powder: 1. Preparation of doping precursor solution: Weigh out SnCl2 according to the atomic molar ratio of Cu:Sn = 98.5:0.5. 1.80 g of 2H2O was dissolved in 100 mL of anhydrous ethanol and stirred for 18 min to obtain a uniform and transparent doped precursor solution.
[0127] 2. Copper powder loaded with doping elements: Weigh 100g of atomized copper powder and add it to the above doping precursor solution. Ball mill for 45min at a ball milling speed of 250r / min and a ball-to-material ratio of 5:1 to obtain loaded copper powder.
[0128] 3. Low-temperature vacuum drying: Place the supported copper powder in a vacuum drying oven and dry it for 3 hours under the conditions of vacuum degree ≤10Pa and drying temperature 60℃ to obtain dried supported copper powder.
[0129] 4. Reducing atmosphere annealing and diffusion: Dry supported copper powder is placed in a tube furnace, and a mixed atmosphere of 95 vol% Ar + 5 vol% H2 is introduced into the tube furnace at a flow rate of 80 mL / min. After the atmosphere is introduced for 30 min, the tube furnace is heated to 400 °C at a heating rate of 3 °C / min, and the supported copper powder is annealed at a constant temperature for 2 hours. After annealing, the supported copper powder is naturally cooled to room temperature to obtain Cu(Sn) solid solution.
[0130] 5. Depolymerization and sieving: The Cu(Sn) solid solution is depolymerized and sieved through a 400-mesh sieve to obtain Sn-doped copper powder.
[0131] (2) Preparation of organic carriers: Weigh out 1 part ethyl cellulose, 6 parts terpineol, and 3 parts butyl carbitol acetate, mix them, heat to 65°C, stir until completely dissolved, filter to remove bubbles, and obtain the organic carrier.
[0132] (3) Preparation of TOPCon photovoltaic copper paste: Weigh out 87 parts by weight of Sn single-doped copper powder, 2 parts by weight of Bi2O3-ZnO-B2O3 system glass powder, 9 parts by weight of organic carrier and 2 parts by weight of additives, add them to a planetary mixer and stir at 450 r / min for 35 min; then grind them with a three-roll mill (pressure 0.4 MPa) until the fineness is ≤5 μm, and degas under vacuum for 18 min to obtain TOPCon photovoltaic copper paste.
[0133] II. Fabrication of stacked electrodes on the back of the TOPCon battery: 1. Printing silver seed layer: Silver paste is screen-printed onto the SiOx / poly-Si passivation layer on the back of the TOPCon battery with a thickness of 2μm, and dried at 150℃ for 6min.
[0134] 2. Overprinting copper paste: The prepared TOPCon photovoltaic copper paste is overprinted on the surface of the silver seed layer with a thickness of 15μm and dried at 150℃ for 2.5min.
[0135] 3. Co-sintering: Under a mixed atmosphere of N2+H2 (oxygen content ≤50ppm), the temperature is increased to 650℃ at a heating rate of 6℃ / min, and sintered at a constant temperature for 6min. Then, it is naturally cooled to room temperature to form a multilayer electrode.
[0136] The contact resistance of the stacked electrode was measured to be 0.08Ω. cm², volume resistivity 3.5 μΩ After baking at 200℃ for 1 hour, the resistivity increased by 12%. The TOPCon battery using this stacked electrode had a fill factor of 82.8% and a battery conversion efficiency loss of 0.10%, which was significantly worse than that of Example 1.
[0137] [Comparative Example 3] The TOPCon photovoltaic copper paste in this comparative example, by mass parts, comprises: 87 parts Sn-In-Ga ternary doped copper powder, 2 parts SiO2-Na2O-CaO system glass powder, 9 parts organic carrier, and 2 parts additives.
[0138] The Sn-In-Ga ternary doped copper powder has an atomic molar ratio of Cu:Sn:In:Ga = 98.5:0.5:0.5:0.5, a D50 of 1.2 μm, an oxygen content ≤0.2 wt%, and a resistivity ≤2.8 μΩ. cm. Atomized copper powder with a D50 of 1.2 μm and an oxygen content ≤0.3 wt% was selected. SnCl2 was used as the doping source. 2H2O, InCl3, GaCl3.
[0139] The glass powder components of the SiO2-Na2O-CaO system have the following mass percentages: SiO2: 50%, Na2O: 30%, CaO: 20%, melting point 700℃, and D50 2.0μm.
[0140] The organic carrier is composed of ethyl cellulose, terpineol, and butyl carbitol acetate in a mass ratio of 1:6:3. The additives are composed of PVP (polyvinylpyrrolidone), polyamide wax, and ascorbic acid in a mass ratio of 2:1:1.
[0141] I. Preparation steps of TOPCon photovoltaic copper paste: (1) Preparation of Sn-In-Ga ternary doped copper powder: The preparation steps are exactly the same as in Example 1.
[0142] (2) Preparation of organic carrier: The preparation steps are exactly the same as in Example 1.
[0143] (3) Preparation of TOPCon photovoltaic copper paste: Weigh out 87 parts of Sn-In-Ga ternary doped copper powder, 2 parts of SiO2-Na2O-CaO system glass powder, 9 parts of organic carrier and 2 parts of additives according to the mass fraction, add them to a planetary mixer and stir at 450 r / min for 35 min; then grind them with a three-roll mill (pressure 0.4 MPa) until the fineness is ≤5 μm, and degas under vacuum for 18 min to obtain TOPCon photovoltaic copper paste.
[0144] II. Fabrication of stacked electrodes on the back of the TOPCon battery: 1. Printing silver seed layer: The preparation steps are exactly the same as in Example 1.
[0145] 2. Overprinted copper paste: Its preparation steps are exactly the same as in Example 1.
[0146] 3. Co-sintering: The preparation steps are exactly the same as in Example 1.
[0147] The contact resistance of the stacked electrode was measured to be 0.10Ω. cm², volume resistivity 3.8 μΩ The resistivity increased by 18% after baking at 200℃ for 1 hour. The TOPCon cell using this stacked electrode had a fill factor of 82.5%, a cell conversion efficiency loss of 0.15%, significant copper diffusion, and performance inferior to Example 1.
[0148] [Comparative Example 4] The TOPCon photovoltaic copper paste in this comparative example, by mass parts, comprises: 87 parts Sn-In-Ga ternary doped copper powder, 2 parts Bi2O3-ZnO-B2O3 system glass powder, 9 parts organic carrier, and 2 parts additives.
[0149] The Sn-In-Ga ternary doped copper powder has an atomic molar ratio of Cu:Sn:In:Ga = 98.5:0.5:0.5:0.5, a D50 of 1.2 μm, an oxygen content ≤0.2 wt%, and a resistivity ≤2.8 μΩ. cm. Atomized copper powder with a D50 of 1.2 μm and an oxygen content ≤0.3 wt% was selected. SnCl2 was used as the doping source. 2H2O, InCl3, GaCl3.
[0150] The Bi2O3-ZnO-B2O3 system has the following glass powder composition by mass percentage: Bi2O3: 60%, ZnO: 20%, B2O3: 20%, melting point 500℃, and D50 2.0μm.
[0151] The organic carrier is composed of ethyl cellulose, terpineol, and butyl carbitol acetate in a mass percentage ratio of 5%, 50%, and 45%, respectively. This organic carrier has a low viscosity and poor film-forming properties.
[0152] The additives are a mixture of PVP (polyvinylpyrrolidone), polyamide wax, and ascorbic acid in a mass ratio of 2:1:1.
[0153] I. Preparation steps of TOPCon photovoltaic copper paste: (1) Preparation of Sn-In-Ga ternary doped copper powder: The preparation steps are exactly the same as in Example 1.
[0154] (2) Preparation of organic carrier: Weigh 0.5 parts of ethyl cellulose, 5 parts of terpineol and 4.5 parts of butyl carbitol acetate, mix them and heat to 65°C, stir until completely dissolved, filter and degas to obtain organic carrier.
[0155] (3) Preparation of TOPCon photovoltaic copper paste: The preparation steps are exactly the same as in Example 1.
[0156] II. Fabrication of stacked electrodes on the back of the TOPCon battery: 1. Printing silver seed layer: The preparation steps are exactly the same as in Example 1.
[0157] 2. Overprinted copper paste: The preparation steps are exactly the same as in Example 1. During the printing process, ink overflow and uneven dispersion occur.
[0158] 3. Co-sintering: The preparation steps are exactly the same as in Example 1.
[0159] The contact resistance of the stacked electrode was measured to be 0.09Ω. cm², volume resistivity 3.6 μΩ cm, after baking at 200℃ for 1 hour, the resistivity increased by 10%. The TOPCon cell using this stacked electrode has a fill factor of 83.0%, a cell conversion efficiency loss of 0.12%, poor copper paste stability, and performance inferior to Example 1.
[0160] Using TOPCon photovoltaic copper paste from Examples 1 to 3 and Comparative Examples 1 to 4 as samples, each sample was printed on the same substrate and relevant performance tests were conducted. The test process is as follows: 1. Resistivity test: The resistance between the two ends of the electrode is tested using a four-probe ohmmeter.
[0161] 2. Using the transmission line model (TLM method), test electrodes with different spacings were fabricated on a silicon wafer / passivation layer / silver seed layer / copper paste electrode structure. The contact resistance was obtained by fitting IV curves, in Ω. cm².
[0162] 3. Printing conditions: The conductive copper paste from the above embodiments and comparative examples was printed onto the back of the silicon wafer using screen printing technology. The seed layer printing screen specifications were 550 mesh / 5μm wire diameter / total thickness 12μm / 12μm aperture; the copper paste printing screen specifications were 640 mesh / 6μm wire diameter / total thickness 15μm / 20μm aperture.
[0163] 4. Electrical performance testing (conversion efficiency): Conducted in a solar simulator under the following conditions: 25℃, M1.5 spectrum, 1.000 KW / m². Reference standard: GB / T6495.1 1996 Photovoltaic Devices, Part 1: Photovoltaic Current Measurement of voltage characteristics.
[0164] 5. High-Temperature Antioxidant Performance Test: The sintered electrode was placed in a 200℃ constant temperature oven for 1 hour, and the resistivity before and after baking was measured. The resistivity increase rate was calculated using the formula: Resistivity increase rate = (ρ after baking) / ... ρfront) / ρfront×100%.
[0165] 6. Metal diffusion test: SEM-EDS surface scanning (Mapping) and SIMS secondary ion mass spectrometry were used to perform elemental analysis on the passivation layer / electrode interface region to quantitatively detect the diffusion concentration of Cu atoms in the SiOx / poly-Si layer, in ppm.
[0166] 7. Printing performance: Observe whether there are broken lines, ink overflow, pinholes, jagged edges, etc. through screen printing, and grade it as excellent / good / poor.
[0167] The performance test data is shown in the table below:
[0168] As can be seen from the table above: 1. Comparing Example 1 with Comparative Example 1 (pure copper powder): the resistivity increased from 4.2 μΩ. cm decreased to 2.9 μΩ The contact resistance decreased significantly, and the copper diffusion rate dropped from 3.2 ppm to 0.8 ppm. Baking at 200℃ reduced the resistivity increase from 25% to 7%, significantly improving oxidation resistance. The fill factor (FF) increased from 82.1% to 84.2%, and the efficiency loss decreased from 0.18% to ≤0.05%. This demonstrates that Sn-In-Ga ternary doping can significantly improve the electronic structure, conductivity, and oxidation resistance of copper powder. Combined with the low-melting-point glass powder and organic carrier of this invention, it further enhances interfacial bonding, inhibits copper diffusion, and ensures printing and storage performance.
[0169] 2. Comparing Example 1 with Comparative Example 2 (Sn monodoping): resistivity and contact resistance further decreased, copper diffusion decreased by approximately 44%, interface peel strength improved, fill factor FF was higher, efficiency loss was smaller, and oxidation resistance was further improved (resistivity increase after baking at 200℃ decreased from 12% to 7%). This indicates that In and Ga, as donor electrons, can enhance the conductivity of copper powder and form a synergistic effect with Sn, with a far superior effect to Sn monodoping. Furthermore, the wetting effect of glass powder and the dispersing effect of organic carrier further optimize interface performance and copper paste stability.
[0170] 3. Comparison of Example 1 with Comparative Example 3 (with an unreasonable glass powder formulation): Comparative Example 3 has higher resistivity and contact resistance, and increased copper diffusion (from 0.8ppm to 2.5ppm); efficiency loss increased from ≤0.05% to 0.15%, and resistivity increased to 18% after baking at 200℃. The core reason is that the melting point of the glass powder in Comparative Example 3 (700℃) is close to the peak sintering temperature, resulting in insufficient melting and an inability to form a dense diffusion barrier layer. Furthermore, its poor wettability leads to poor interfacial bonding and intensified copper diffusion. In contrast, the Bi2O3-ZnO-B2O3 system glass powder in Example 1 has a melting point of 450~550℃, allowing for sufficient melting to form a dense barrier layer. Simultaneously, it wets the copper powder and silver seed layer, optimizing interfacial performance and protecting the passivation layer.
[0171] 4. Comparison of Example 1 with Comparative Example 4 (with an unreasonable organic carrier formulation): The copper paste in Comparative Example 4 exhibited ink overflow during printing and severe sedimentation after 72 hours of storage, with high resistivity and contact resistance, resulting in an efficiency loss of 0.12%. The core reason is that the organic carrier in Comparative Example 4 had too low an ethyl cellulose content and insufficient viscosity, leading to poor film-forming properties and dispersibility. Copper powder and glass powder easily precipitated, causing ink overflow during printing. Simultaneously, the organic carrier had poor volatility, and residual impurities affected electrode performance. In contrast, the organic carrier formulation in Example 1 was reasonable, with viscosity, dispersibility, and volatility all suitable for the preparation and application requirements of copper paste, ensuring the printing performance and storage stability of the copper paste. Furthermore, there were no residues after sintering, which did not affect electrode performance.
[0172] 5. Comparison of Examples 1 to 3: Example 1 (medium doping, medium glass powder content, medium carrier content) and Example 3 (higher doping, less glass powder content, less carrier content) can balance six core properties: conductivity, oxidation resistance, interfacial bonding, copper diffusion suppression, printing performance, and storage stability. Among them, Example 3 has the lowest resistivity (2.7 μΩ). With the lowest doping concentration (cm), the smallest copper diffusion (0.6ppm), and the highest fill factor (FF) (84.5%), it is best suited for the mass production requirements of TOPCon stacked electrodes. Example 2 (low doping concentration, higher glass powder concentration, and higher carrier concentration) has slightly inferior performance, but still meets the requirements of industrial production and is suitable for scenarios with stricter cost control.
[0173] The above are merely specific embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A Sn-In-Ga ternary doped copper powder, characterized in that, The material includes copper powder, tin, indium, and gallium. The Sn-In-Ga ternary doped copper powder is a solid solution formed by the tin, indium, and gallium adhering to the surface of the copper powder in atomic form. The atomic molar ratio of each element in the Sn-In-Ga ternary doped copper powder is Cu:Sn:In:Ga=(98.0~99.2):(0.2~0.8):(0.2~0.8):(0.2~0.8).
2. The Sn-In-Ga ternary doped copper powder as described in claim 1, characterized in that, The particle size D of the copper powder 50 The particle size is 0.6μm~2.0μm, and the oxygen content of the copper powder is ≤0.3wt%.
3. A method for preparing Sn-In-Ga ternary doped copper powder as described in any one of claims 1 or 2, characterized in that, Includes the following steps: S1: Dissolve tin salt, indium salt and gallium salt in a solvent and mix them evenly to obtain a doping precursor solution; S2: After adding copper powder to the doping precursor solution, ball milling is performed to adsorb tin ions, indium ions and gallium ions on the surface of the copper powder to obtain supported copper powder. S3: Dry the supported copper powder; S4: Under a reducing atmosphere, the supported copper powder is annealed to allow tin, indium and gallium to diffuse and solidify on the surface of the copper powder in atomic form, thereby obtaining a Cu(Sn-In-Ga) solid solution. S5: The Cu(Sn-In-Ga) solid solution is depolymerized and sieved to obtain Sn-In-Ga ternary doped copper powder.
4. The preparation method according to claim 3, characterized in that, In step S2 above, a first dispersant is also added to the doping precursor solution.
5. The preparation method according to claim 3, characterized in that, In step S3 above, the supported copper powder is vacuum dried under the following conditions: vacuum degree ≤10Pa, drying temperature 50℃~70℃, and drying time 2 hours~4 hours.
6. The preparation method according to claim 3, characterized in that, In step S4 above, the specific steps for annealing the supported copper powder include: The supported copper powder is placed in a tube furnace, and then a reducing gas is introduced into the tube furnace to remove the air. The tube furnace is heated to 280°C to 450°C at a heating rate of 2°C / min to 5°C / min, and the supported copper powder is annealed at a constant temperature for 1 hour to 3 hours. After annealing, the supported copper powder is allowed to cool naturally to room temperature.
7. The preparation method according to claim 6, characterized in that, The reducing gas is a mixture of 95 vol% Ar and 5 vol% H2.
8. A TOPCon photovoltaic copper paste, characterized in that, The TOPCon photovoltaic copper paste comprises, by weight, 84-90 parts of Sn-In-Ga ternary doped copper powder, 1-3 parts of glass powder, 7-12 parts of organic carrier, and 0.5-2 parts of additives; the organic carrier comprises organic resin and organic solvent, and the additives comprise thixotropic agent, second dispersant, and reducing agent; the Sn-In-Ga ternary doped copper powder is the Sn-In-Ga ternary doped copper powder as described in any one of claims 1 or 2, or is prepared by the preparation method as described in any one of claims 3-7.
9. The TOPCon photovoltaic copper paste as described in claim 8, characterized in that, The glass powder is a Bi2O3-ZnO-B2O3 system glass powder, and the melting point of the Bi2O3-ZnO-B2O3 system glass powder is 450℃~550℃; by mass percentage, the Bi2O3-ZnO-B2O3 system glass powder comprises: 55%~65% bismuth oxide, 15%~25% zinc oxide, and 10%~20% boron oxide.
10. The TOPCon photovoltaic copper paste as described in claim 8, characterized in that, The organic carrier contains 6% to 12% organic resin and 88% to 94% organic solvent by mass. And / or, the mass ratio of the second dispersant, thixotropic agent and reducing agent in the additive is (1.5~2.5):(0.8~1.2):(0.8~1.2).
11. The TOPCon photovoltaic copper paste as described in claim 8, characterized in that, The organic resin includes at least one of ethyl cellulose, cellulose acetate butyrate, polyvinyl butyral resin, acrylic resin, rosin resin, and epoxy resin; And / or, the organic solvent includes at least two of dibutyl phthalate, terpineol, benzyl alcohol, diethylene glycol dibutyl ether, diethylene glycol butyl ether, dodecyl alcohol ester, and diethylene glycol butyl ether acetate; And / or, the thixotropic agent includes at least one of polyamide wax, polyethylene wax, hydrogenated castor oil, and fumed silica; And / or, the second dispersant comprises at least one of fatty acid polyoxyethylene ether, shea butter-based propylene diamine oleate, lecithin, oleic acid, polyvinylpyrrolidone, and polyethylene glycol; And / or, the reducing agent includes at least one of ascorbic acid and sodium hypophosphite.
Citation Information
Patent Citations
Lasting machine
CA38105A
Tungsten-coated copper anti-oxidation material and preparation method thereof
CN119910179A
Tin-coated copper powder and preparation method and application thereof
CN121911880A
Preparation method of photovoltaic cell, sintering equipment, photovoltaic cell and photovoltaic module
CN122094223A